The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1080/10926771.2017.1357060
|View full text |Cite
|
Sign up to set email alerts
|

Improving Interaction Competencies With Children—A Pilot Feasibility Study to Reduce School Corporal Punishment

Abstract: High prevalence rates of corporal punishment in schools worldwide and the associated negative mental health issues show the need for interventions addressing this problem. Yet, so far there are very few intervention studies aimed at altering corporal punishment administered by teachers, particularly in low-or middle-income countries. To conduct a feasibility study of the newly developed intervention approach, Interaction Competencies with Children for Teachers (ICC-T)-a training workshop designed to prevent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(70 citation statements)
references
References 34 publications
(59 reference statements)
7
57
0
4
Order By: Relevance
“…ICC-T aims to enable teachers to use nonviolent disciplinary measures and to strengthen their competencies in non-violent interactions by introducing essential interaction competencies with children into the daily work of teachers. The pilot study demonstrated the feasibility of ICC-T at the primary school level [6] and the CRCT provided initial evidence of the effectiveness of the preventative intervention at the secondary school level: The use of violent discipline by teachers (self-reported and reported by students) was reduced in the intervention schools compared to control schools. Furthermore, teachers in the intervention schools reported less positive attitudes towards the use of violent discipline in intervention schools at follow-up compared to control schools [1].…”
Section: Intervention To End Violence By Teachers Against Children Inmentioning
confidence: 92%
See 3 more Smart Citations
“…ICC-T aims to enable teachers to use nonviolent disciplinary measures and to strengthen their competencies in non-violent interactions by introducing essential interaction competencies with children into the daily work of teachers. The pilot study demonstrated the feasibility of ICC-T at the primary school level [6] and the CRCT provided initial evidence of the effectiveness of the preventative intervention at the secondary school level: The use of violent discipline by teachers (self-reported and reported by students) was reduced in the intervention schools compared to control schools. Furthermore, teachers in the intervention schools reported less positive attitudes towards the use of violent discipline in intervention schools at follow-up compared to control schools [1].…”
Section: Intervention To End Violence By Teachers Against Children Inmentioning
confidence: 92%
“…Apart from the legal intervention strategies, the school-based preventative intervention approach Interaction Competencies with Childrenfor Teachers (ICC-T) has been evaluated in a cluster randomized controlled trial (CRCT) in secondary schools and in a pilot study with one selected primary school in Tanzania [1,6]. ICC-T is based on attachment, behavioral, and social learning theories.…”
Section: Intervention To End Violence By Teachers Against Children Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the existence of different national and international intervention strategies to end violent discipline by teachers, the prevalence of the use of violent discipline by teachers is still reported globally (3)(4)(5). In many countries in Sub-Saharan Africa, including, for example, Tanzania, violent discipline by teachers is still legal and considered by teachers as being a necessary and effective disciplinary tool to control student behaviour (6).…”
Section: Introductionmentioning
confidence: 99%